2014
DOI: 10.1007/s11657-014-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral insufficiency fractures and spontaneous osteonecrosis of the knee may not be related to osteoporosis

Abstract: We conclude that osteoporosis is not the underlying cause of this disorder in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
3
25
0
1
Order By: Relevance
“…The high frequency of osteopenia or osteoporosis among our study population, especially in comparison to previously reported rates of osteopenia or osteoporosis in normal adult populations, supports that the impaired bone architecture along the load-bearing surfaces is likely a risk factor for insufficiency fracture [28,29]. However, the degree of abnormality (osteopenia versus osteoporosis) to predispose to fracture remains controversial [10,30]. Additionally, in our study, female gender did show a modest association with progression of FCIF to TKA.…”
Section: Discussionsupporting
confidence: 78%
“…The high frequency of osteopenia or osteoporosis among our study population, especially in comparison to previously reported rates of osteopenia or osteoporosis in normal adult populations, supports that the impaired bone architecture along the load-bearing surfaces is likely a risk factor for insufficiency fracture [28,29]. However, the degree of abnormality (osteopenia versus osteoporosis) to predispose to fracture remains controversial [10,30]. Additionally, in our study, female gender did show a modest association with progression of FCIF to TKA.…”
Section: Discussionsupporting
confidence: 78%
“…Osteophytes were excluded for determining the medial margin. The measurement of 3 mm or more was considered meniscal extrusion …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, meniscal extrusion is associated with the progression of osteoarthritis . A recent study has demonstrated high incidence of medial meniscus extrusion in the knee with SONK . However, no information is available on the relationship between medial meniscus extrusion and the severity of SONK.…”
Section: Introductionmentioning
confidence: 99%
“…However, review of the available literature suggested that an increase in duties requiring prolonged standing beginning 5 months before the injury was the key inciting factor, and that the subchondral fractures would probably have occurred in the absence of osteoporosis 3 4. The patient's significant decrease in hip bone density and quadriceps atrophy were probably due to decreased ipsilateral weight bearing in the 5 months since the injury, in addition to normal bone density loss during the menopausal transition.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis may range from full recovery to rapidly escalating joint destruction 2. A case series of 32 patients (mean age 70 years, 5 patients osteoporotic) with knee insufficiency fractures concluded that osteoporosis is not the underlying cause of subchondral insufficiency fractures in the majority of patients 3. Instead, these fractures are typically precipitated by athletic or overuse injuries or trauma (including surgical interventions) to the knee, and they may occur on the non-weight bearing surface of the femur 4 5.…”
Section: Introductionmentioning
confidence: 99%